An Error Analysis of Student's Reading Ability On News Item Text : An Error Analysis of Student's Reading Ability On News Item Text - Fahira Zahra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2023)
An Error Analysis of Students’ Reading Ability on News Item text Fahira Zahra1, Ashari P Swondo2 English Language Education Study Program, Faculty of Social Science and Education corresponding authorEmail: iamrara@gmail.com, arieswondo770809@gmail.co ABSTRACT Reading is one activity that can make a person increase knowlodege. Reading aloud is one of type in reading skills. Reading aloud is an activity designed to practice students to read aloud with correct pronunciation. This research was aimed to find out the errors appeared in students’ reading, especially in news item text and causes of errors made by students in reading news item text. This research was conducted in SMA Swasta Imelda Medan of XII grade students of 2023/2024 This research was carried out using qualitative method which used transcript instruments from the results of students’ reading in news item text. Then, from the results of the transcript read by the students, the researchers examined them to find out what errors often appeared in students’ reading, especially in news item text. And for the causes, the transcript result interview, the researchers examined them to find out what causes of errors that made by students in reading news item text. The results of this research show that errors in students’ reading include subtitution, addition, omission, repetition, reversal and unknown word. Then the results of this research also show that the most frequent errors in students’ reading are subtitution with a total of 400 errors with percentage 37,8%, the second is unknown word error with a total of 313 with percentage 29,5%, the third is omission error with a total of 210 with percentage 19,8%, the fourth is addition error with a total of 62 with percentage 5,8%, the fifth is repetition error with a total of 61 with percentage 5,7% , and the last is reversal error with a total of 12 with percentage 1,1%. This problem influenced by cognitive and psychological factors. The students felt lack of vocabulary, lack of pronunciation, feeling nervous and lack of confidence. Keywords: error analysis, students’ reading ability, news item text INTRODUCTIONThe purpose of teaching English in schools is to improve the language skills of students. Students learning English should master four main skills, namely listening, speaking, reading and writing. The four basic English skills are divided into two categories, namely receptive skills and productive skills. Reading and listening are considered receptive skills, while speaking and writing are considered productive skills. Reading is one activity that can make a person increase knowledge. According to (L.Stoller, 2002) taken from article citation (Nurmalasari, Kania 2019) reading is the ability to draw meaning from the printed page and interpret this information appropriately. In teaching reading skills can divided into; reading aloud, silent reading, reading comprehension, and independent reading. Reading aloud is an activity designed to train students to read aloud with correct pronunciation. Reading aloud usually using the skills of look and say, aimed at being able to pronounce English words, phrases and sentences correctly. The purpose of reading is not only to understand the text, but also to inform the listener. Mckeown and Gentilucci (2007) claim that reading aloud is a method of measuring the cognitive reading process and it is used to measure the competence of reading skill.During internship program, the researcher saw that students are interested in learning that involves action rather than explanation a material. Students prefer when the teacher involved students in a material that will be explained. Reading aloud is one of the methods used by researcher in implementing learning, and some students looked enthusiastic in reading aloud. But, there are some students who do not seem enthusiastic in learning reading aloud because they lack self-confidence and afraid to make mistake in saying word. Actually, the researcher felt that the students' interest in reading is quite good. When learning English, the researcher used news item text in reading aloud. The researcher read it first and students pay attention to it. After that, the researcher asked the students to read aloud one by one. When students read, the researcher saw that some students made mistakes in reading and had difficulty in reading. In this case, the researcher choosen news item text in research. News item text in forms the readers, listeners or viewers about an event of the day, which is considered newsworthy or important. Teaching news item text is not always simple as most of people think especially in reading news item text like a news anchor. The reading aloud a news item text help the students to understand the meaning of the text, getting new vocabulary, improving pronunciation, improving confidence and make students active during learning. In reading aloud, students could be more attentive to reader. When the students read in English, they will have errors in reading English text. Many types of errors are made by students when they read news item text, including subtitution, addition, ommision, repetition, reversal and unknown word. There are several previous studies that related to the error analysis in reading news item text. The first related research conducted by Ahmad Saifudin (2019) with his research title, Error Analysis on Grammar in Writing News Item Text Made by The First Year Students of MA Syekh Subakir Nglegok Blitar. In this research, the researcher’s research was qualitative. The subjects of the research covered the first year students of MA Syekh Subakir Nglegok. After researcher did observation and have the result that found the most frequent error types which made by the tenth grade students of MA Syekh Subakir Nglegok was noun error or errors of ordering of noun phrase.There were 21 errors in ordering of noun phrase. The second errors is verb selection. The third errors is verb addition. The fourth errors is verb of subtitution. The fifth errors is preposition addition.It can be taken conclusion that the students still have difficulties in grammar.The second related research was written by Mutiana Nurmalasari and Ikeu Kania (2019) with the title, The Analysis of Students’ Pronunciation Errors in Reading Aloud. In this research, the researcher used the qualitative research. The subjects of this research were secong grade of SMAN 13 Garut. After the researchers did observation and have the result that found 97 pronunciation errors from 7 students that had been tested. The researchers found the students’ pronunciation errors in six part of speech; nouns, verbs, adjectives, adverbs, prepositions and conjunction.Those several previous study have been conducted. The focus of the first research was on error analysis on grammar in writing news item text and its data were collected by observation data and students’ test score from about 35 students which found the most frequent error types which made by the tenth grade students was noun error or errors of ordering of noun phrase. There were 21 errors in ordering of noun phrase. The second previous research focused on pronunciation errors. The researcher found 97 pronunciation errors from 7 students that had been tested. The researchers found the students’ pronunciation errors in six part of speech; nouns, verbs, adjectives, adverbs, prepositions and conjunction. The difference of this research and those previous researches are the research design, the concern of material and the place where the research will be conducted. This research focuses on identifying an error analysis on the use news item text about natural disaster in student’s reading text and the researcher focuses on reading aloud. This research will take place at SMA Swasta Imelda Medan and the research subject of this study is the XII grade students at SMA Swasta Imelda Medan. Literature Review Kennedy (1981: 5) says that reading is the ability of an individual to recognize a visual form, associate the form with a sound and or meaning acquired in the past, based on past experiences, understand and interpret its meaning.. In addition, Badrawi (1995:16) means that when someone is reading, his brain will work actively. The reader brings all kinds of knowledge has about the world (schemata) and relates to the text that reading at the moment so that able to understand the writer’s ideas. Reading is not only looking at word in the form of graphic symbols but also getting meaning from word to word or line to line to understand what we read. It means that reading is a process to understand the content and to get information.Kailani (1998: 281) states that reading aloud is characterized by the clear articulation of words, flexibility in stress, intonation and rhythm, and the effective use of pauses. Reading aloud is the activity of reading by voicing the text, the students read with the right words and intonation to get more information, vocabulary, and improve their pronunciation. Mckeown and Gentilucci (2007) claim that reading reading aloud is a method of measuring the cognitive reading process and it is used to measure the competence of reading skills. Applying the reading aloud strategy will prompt the students to improve their reading skills.Error analysis is considered as one of the best ways that describes and explains errors made by the learners who study Englih language as a second or foreign language. James (1998) defines error analysis as the process of determining the incidence, nature, causes and consequences of unsuccessful language. According to H Douglas Brown (2007) ‘’ Errors analysis is the fact that the learners do make errors and that these errors can be observed, analyzed and classified to reveal something of the system operating within the learner led to surge of study of learners ‘’error’’.According to William Scott gray, states that in a reading error, there are six categories of errors made by the reader. The six categories are: subtitution, addition, omission, repetition, reversal and unknown word. According to Clark and clark (1977: 271), there are two sources of errors, as follow; cognitive reason and psychological or affective reason. According to Eltis (1990: 15-18) news item text is to inform readers about events of the day which are consider newsworthy or important. From the definition above, it can be conclude that a news item is factual text which inform readers events of the day which are considered newsworthy or important. According to Eltis (1990: 15-18) The generic structure of news item text, they are; 1. Newsworthy EventsThe newsworthy event stage is put at the beginning because the reader needs to get the angel on the events before deciding whether to read on. This stage gives information about who, when, where and what the events occurred. 2. Background Events Background events in the news story gives information about the events that lead up to. It can include information about how and why the events occurred, the circumstances surrounding the crisis. After the lead up events, the news writer will often give more information about what happened during and after the crisis what is likely to happen in the future. 3. Sources It directly follows each of background events. It contains a comment given by person or participant, or authority on the subject. The example of news item text in reading aloud about natural disaster with title ‘’ Floods hit dozens of areas in Jakarta’’ Table 1 Example News Item Text RESEARCH METHODThe type of this research is qualitative research. This research used descriptive qualitative method. In writing this research, the researcher will collect, clasify,analyse, and draw a conclusion based on the data analyse without making generalization. Thus, the researcher would know the types of reading errors made by students in reading news item text and causes of the errors. According to Cresswell (2018), Qualitative research is an approach for exploring and understanding the meaning individuals or group ascribe to social or human problem.Simply, qualitative research is often called naturalistic inquiry, or field study. It means qualitative is a research design where the researcher presenting the data with using description.The research will be conducted at SMA Swasta Imelda Medan academic year 2022/2023. It is located at Jalan Bilal, Kecamatan Medan Timur, Medan, Sumatera Utara. The subject of this research is the XII grade students of SMA Swasta Imelda Medan in academic year 2023/2024.Data collection techniques according to As John W.Cresswell (2009) acknowledges, data collection requires observation, interviews, documentation and visual materials. In this research, researcher collected data using observation, interviews, documentation and visual materials. To collect the data of this research, the researcher used the following steps; the researcher prepares the instrument of the test. Instrument of the test consists of researcher, recording equipment, stationery, interview text and documentation, the researcher comes to school and ask for permission to the principal of SMA Swasta Imelda Medan to do research, the researcher makes a schedule with the English teacher of SMA Swasta Imelda Medan to conduct the test, the researcher gives a test to the XII grade students of SMA Swasta Imelda Medan, the students starts the test one by one to reading aloud news item text test and record it by handphone recorder, after that, the researcher will identify and analyze based on Asmani’s reading aloud assessment to know the kind of errors, and in order to answer the causes of errors in reading ability, the researcher will interview the students as personally, from this, the researcher knows the kind of errors and the causes of errors made by students in reading aloud focused on news item text about natural disasters.After data is collected, organized, and stored, the researcher have to identify the meanings and significance of the information. According to Cresswell (2012) identifies four steps for this phase; Prepare data, Analyze data, report result and interpret the result. 1.) Process and prepare data for analysis, 2) Read the entire data or analyze in depth to describe all the information and the identify it. 3) Integrate data and summarize for audience, indicate how these descriptions and themes will be restated in the narrative/qualitative research, 4) The final step is to interpret the data. To find the percentage of the students , this is the formula of calculating the percentage is as the following. fP = x 100%n Note:P = Percentage of categoryf = Frequency of the categoryn = Total amount for the category RESULTS AND DISCUSSION The data were taken from the student’s test to read news item text. The researcher discussed about the error on students’ reading news item text that focused on the kinds of error. The students’ error in reading was the resource of the data which the researcher had implemented in the classroom. In reading, most students made abundant of reading errors. Table 2 Classification of ErrorsNoName (Initial)Classification of Errors SubtitutionAdditionOmissionRepetitionReversalUnknown WordsTotal 1.MP4120119 2.MM19412301856 3.NI154111628 4.HW2456112057 5.NS2063001443 6.SK37611213188 7.RF2854611357 8.SK1812101234 9.DL181141530 10.FF130130623 11.NA29691222280 12.ZN2927402971 13.RP11517303066 14.MDR1935411749 15.AT2335402257 16.RA19123502573 17.NS2315311346 18.CC102922119126 19.SR223311939 20.AP193120126 Total4006221061123131058 From the table above, the researcher found that the total errors made by students are 1058 by each kinds of errors as the following table, it shows that the occurrences of subtitution error was 400, the occurrences of addition error was 62, the occurrences of omission error was 210, the occurrences of repetition error was 61, the occurrences of reversal error was 12, and the occurrences of unknown words error was 313. Occurrences which totaled 1058.The next step is to analyze the result of data. Here are data analysis about students’ errors in reading news item text on the test and causes of the errors, which have been done by students in XII IPS class. Table 3 The Identification of the Errors of Students 1Paragraph of the TestIdentification of ErrorDescription Error Classification Correction TitleFluds, hits, DozenSubtitution, Addition, OmissionFloods /ˈfɫədz/, Hit /ˈhɪt/, Dozens /ˈdəzənz/ 1Japa, Agency/ˈadʒənsi/ KatalumpaSubtitution, ReversalJava /ˈdʒɑvə/, Agency /ˈeɪdʒənsi/, Katulampa 2ReportedOmissionReportedly /ˌɹiˈpɔɹtɪdli/ 3StetusSubtitutionStatus /ˈstætəs/ Table 4 The Identification of the Errors of Student 2Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningViewrs, English /ˈeŋɡɫɪʃ/, Henline, bringOmission, SubtitutionViewers /ˈvjuɝz/, English /ˈɪŋɡɫɪʃ/, Headline /ˈhɛdˌɫaɪn/, bringing TitleFluds, it, areaksSubtitution, Omission, Addition Floods /ˈfɫədz/, Hit/ˈhɪt/, areas /ˈɛɹiəz/ 1Sains, ai,slunsSubtitution, unknown words, additionSince /ˈsɪns/, it /ˈɪt/, Sluice /ˈsɫus/ 2Raiver, anits, subdistriSubtitution, OmissionRiver /ˈɹɪvɝ/, Units /ˈjunɪts/, Subdistrict 3Agency /ˈadʒənsi Manggari,inandesSubtitution, Omission, Unknown WordsAgency /ˈeɪdʒənsi/, Manggarai, Inundated /ˈɪnənˌdeɪtɪd/ ClosingNes, UpdateUnknown Words, OmissionNews /ˈnjuz/, Updates /ˈəpˌdeɪts/ Table 5 The Identification of the Errors of Student 3Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/, YorSubtitution, Unknown WordsEnglish /ˈɪŋɡɫɪʃ/, You /ˈju/ TitleAreas /ˈaɹəaz/SubtitutionAreas /ˈɛɹiəz/ 1Frider, SluisUnknown Words, AdditionFriday /ˈfɹaɪˌdeɪ/, Sluice /ˈsɫus/ 2SoutSubtitutionSouth /ˈsaʊθ/ 3Rajawati, alert /aˈɫɝt/Reversal, SubtitutionRawajati, Alert /əˈɫɝt/ ClosingLesUnknown WordsLatest /ˈɫeɪtəst/ Table 6 The Identification of the Errors of Student 4Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningHel, newUnknown Words, OmissionHeadline /ˈhɛdˌɫaɪn/, News /ˈnjuz/ Title Fol, dit , DozenUnknown words, Subtituton , omissionFlood /ˈfɫəd/, Hit /ˈhɪt/, Dozens /ˈdəzənz/ 1Dozen, Naighborhods, anobed, sluns…slus, gateseOmission, subtitution, unknown words, repetition, additionDozens /ˈdəzənz/, Neighborhoods /ˈneɪbɝˌhʊdz/, announced /əˈnaʊnst/, sluice /ˈsɫus/, gates /ˈɡeɪts/ 2Rivers, overwaitAddition, unknown wordsRiver /ˈɹɪvɝ/, overflowed /ˌoʊvɝˈfɫoʊd/ 3Rajawati, Reporter, hertReversal, SubtitutionRawajati, reported /ˌɹiˈpɔɹtɪd/, heart /ˈhɑɹt/ ClosingUpdate, otOmission, unknown wordUpdates /ˈəpˌdeɪts/, Out /ˈaʊt/ Table 7 The Identification of the Errors of Student 5Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningLets, English /ˈeŋɡɫɪʃ/, News /ˈnjez/Unknown Words,SubtitutionLatest /ˈɫeɪtəst/, English /ˈɪŋɡɫɪʃ/, News /ˈnjuz/ TitleHait,eresAddition, unknown wordsHit /ˈhɪt/, areas /ˈɛɹiəz/ 1Wis, slutsSubtitution, additionWest /ˈɛɹiəz/, Sluice /ˈsɫus/ 2OnitsSubtitutionUnits /ˈjunɪts/ 3Meter /ˈmetɝ/,, subdistrictSubtitution, OmissionMeter /ˈmitɝ/, Subdistricts ClosingNews /ˈnjez/, lesSubtitution, unknown wordNews /ˈnjuz/, latest /ˈɫeɪtəst/ Table 8 The Identification of the Errors of Student 6Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningViews, English /ˈeŋɡɫɪʃ/,Omission,SubtitutionViewers /ˈvjuɝz/, English /ˈɪŋɡɫɪʃ/, TitleFluts, EinotsSubtitution , unknown wordsFloods /ˈfɫədz/, announced /əˈnaʊnst/ 1Dozen, distaiterOmission, unknown wordsDozens /ˈdəzənz/, Disaster /dɪˈzæstɝ/ 2Rivers, repotlyAddition, OmissionRiver /ˈɹɪvɝ/, Reportedly /ɹiˈpɔɹtədɫi/ 3Rajawati, SoutReversal, SubtitutionRawajati, South /ˈsaʊθ/ ClosingNews /ˈnjez/ , lesSubtitution, unknown wordNews /ˈnjuz/, latest /ˈɫeɪtəst/ Table 9 The Identification of the Errors of Student 7Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningHidlin, news /ˈnjez/Unknown words ,SubtitutionHeadline /ˈhɛdˌɫaɪn/, news /ˈnjuz/ TitleFluts, DlozesSubtitution , unknown wordsFloods /ˈfɫədz/, dozens /ˈdəzənz/ 1Dozen, neigbrotesOmission, unknown wordsDozens /ˈdəzənz/, Neighborhoods /ˈneɪbɝˌhʊdz/ 2Raiver, repotlySubtitution, OmissionRiver /ˈɹɪvɝ/, Reportedly /ɹiˈpɔɹtədɫi/ 3Rajawati, weterReversal, SubtitutionRawajati, Water /ˈwɔtɝ/ ClosingNews /ˈnjez/, lesSubtitution, unknown wordNews /ˈnjuz/, latest /ˈɫeɪtəst/ Table 10 The Identification of the Errors of Student 8Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningLiders, news /ˈnjez/Unknown words ,SubtitutionLatest /ˈɫeɪtəst/, news /ˈnjuz/ TitleFluts, HisSubtitution, Unknown wordsFloods /ˈfɫədz/, Hit /ˈhɪt/ 1hive,raisingSubtitutionHeavy /ˈhɛvi/, rising /ˈɹaɪzɪŋ/ 2Unit, Floo…floodedSubtitution, RepetitionUnit /ˈjunɪt/, Flooded /ˈfɫədəd/ 3Ainendid, oderUnknown words, SubtitutionInundated /ˈɪnənˌdeɪtɪd/, other /ˈəðɝ/ ClosingNews /ˈnjez/, litsSubtitution, unknown wordNews /ˈnjuz/, latest /ˈɫeɪtəst/ Table 11 The Identification of the Errors of Student 9Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningHidlain, letsSubtitution, unknown words,Headline /ˈhɛdˌɫaɪn/, Latest /ˈɫeɪtəst/, TitleFlutsSubtitution, Floods /ˈfɫədz/, 1Hive, lev…levelsSubtitution, repetitionHeavy /ˈhɛvi/, levels /ˈɫɛvəɫz/ 2Owerflowed, letsSubtitution, unknown wordsOverflowed /ˌoʊvɝˈfɫoʊd/, least /ˈɫist/ 3Rajawati, slutsReversal , additionRawajati, sluice /ˈsɫus/ ClosingEnglish /ˈeŋɡɫɪʃ/, letsOmission, unknown wordEnglish /ˈɪŋɡɫɪʃ/, latest /ˈɫeɪtəst/ Table 12 The Identification of the Errors of Student 10Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/, letsSubtitution, unknown words,English /ˈɪŋɡɫɪʃ/ ,Latest /ˈɫeɪtəst/, TitleFlutsSubtitution, Floods /ˈfɫədz/, 1Faraday, DisainUnknown wordsFriday /ˈfɹaɪˌdeɪ/, Disaster /dɪˈzæstɝ/ 2Raiver, reportlySubtitution, OmissionRiver /ˈɹɪvɝ/, reortedly /ɹiˈpɔɹtədɫi/ 3Rajawa…rawajati, soutRepetition , subtitutionRawajati, south /ˈsaʊθ/ ClosingEnglish /ˈeŋɡɫɪʃ/, letsSubtitution, unknown wordEnglish /ˈɪŋɡɫɪʃ/, latest /ˈɫeɪtəst/ Table 13 The Identification of the Errors of Student 11Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/, letsSubtitution, unknown words,English /ˈɪŋɡɫɪʃ/ ,Latest /ˈɫeɪtəst/, TitleFlood, DuzenOmission,SubtitutionFloods /ˈfɫədz/, Dozens /ˈdəzənz/ 1Inended, anocationUnknown wordsInundated /ˈɪnənˌdeɪtɪd/, Announced /əˈnaʊnst/ 2Ciwuling, forgetReversal, Unknown wordsCiliwung, flooded /ˈfɫədəd/ 3Rajawa…rawajati, GondangdiReversal, omissionRawajati, Gondangdia ClosingEnglish /ˈeŋɡɫɪʃ/, letsSubtitution, unknown wordEnglish /ˈɪŋɡɫɪʃ/, latest /ˈɫeɪtəst/ Table 14 The Identification of the Errors of Student 12Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/, headSubtitution, unknown words,English /ˈɪŋɡɫɪʃ/ ,Headline /ˈhɛdˌɫaɪn/ TitleDozen,FloodOmission,SubtitutionDozens /ˈdəzənz/ , Floods /ˈfɫədz/ 1Neighborhods /ˈneɪborhodz/SubtitutionNeighborhoods /ˈneɪbɝˌhʊdz/ 2OverlofetUnknown wordsOverflowed /ˌoʊvɝˈfɫoʊd/ 3InteidedReversal, omissionInundated /ˈɪnənˌdeɪtɪd/ ClosingToday, letsSubtitution, unknown wordToday /tuˈdeɪ/, latest /ˈɫeɪtəst/ Table 15 The Identification of the Errors of Student 13Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEveryone, henglaiunknown wordsViewers /ˈvjuɝz/ ,Headline /ˈhɛdˌɫaɪn/ TitleDosen,Flood Subtitution ,OmissionDozens /ˈdəzənz/ , Floods /ˈfɫədz/ 1Neighborhods/ˈneɪborhodz/ hevenSubtitution, Unknown wordsNeighborhoods /ˈneɪbɝˌhʊdz/ heavy /ˈhɛvi/ 2ClinungUnknown wordsCiliwung 3Rajawati, SubdistriReversal, omissionRawajati, subdistrict ClosingGreen, letsunknown wordGreat /ˈɡɹeɪt/ ,latest /ˈɫeɪtəst/ Table 16 The Identification of the Errors of Student 14Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningLets, bringingsunknown words, AdditionLatest /ˈɫeɪtəst, bringing /ˈbɹɪŋɪŋ/ TitleFlutsSubtitutionFloods /ˈfɫədz/ 1Dozen, UpstreamingOmission, additionDozens /ˈdəzənz/, upstream /ˈəpˈstɹim/ 2Units /ˈunit/Subtitution Unit /ˈjunɪt/ 3Rajawati, SubdistrictReversal, subtitutionRawajati, subdistrict ClosingLetsunknown word,latest /ˈɫeɪtəst/ Table 17 The Identification of the Errors of Student 15Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningLas, English /ˈeŋɡɫɪʃ/unknown words, SubtitutionLatest /ˈɫeɪtəst/, English /ˈɪŋɡɫɪʃ/ TitleHinsUnknown wordsHit ˈhɪt/ 1DozenOmission Dozens /ˈdəzənz/ 2Sout Subtitution South /ˈsaʊθ/ 3Her Unknown wordsHeart /ˈhɑɹt/ ClosingWeder unknown word, Watching /ˈwɑtʃɪŋ/ Table 18 The Identification of the Errors of Student 16Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningLas, English /ˈeŋɡɫɪʃ/unknown words, SubtitutionLatest /ˈɫeɪtəst/, English /ˈɪŋɡɫɪʃ/ TitleAreas /ˈaɹəaz/Subtitution Areas /ˈɛɹiəz/ 1SainsAdditionSince /ˈsɪns/ 2SounUnknown wordsSouth /ˈsaʊθ/ 3Area /ˈaɹəa/OmissionArea /ˈɛɹiə/ ClosingLets, gretunknown word, subtitutionLatest /ˈɫeɪtəst/, great /ˈɡɹeɪt/ Table 19 The Identification of the Errors of Student 17Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/SubtitutionEnglish /ˈɪŋɡɫɪʃ/ TitleDozen, areas /ˈaɹəaz/Omission, Subtitution Dozens /ˈdəzənz/ , areas /ˈɛɹiəz/ 1SainsAdditionSince /ˈsɪns/ 2SoutUnknown wordsSouth /ˈsaʊθ/ 3Rajawati, meter /ˈmetɝ/Reversal, subtitutionRawajati, meter /ˈmitɝ/ ClosingLets, English /ˈeŋɡɫɪʃ/unknown word, subtitutionLatest /ˈɫeɪtəst/, English /ˈɪŋɡɫɪʃ/ Table 20 The Identification of the Errors of Student 18Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish, henSubtitution, Unknown wordsEnglish /ˈɪŋɡɫɪʃ/, headline /ˈhɛdˌɫaɪn/ TitleAll of titleOmissionFloods hit dozens of areas in jakarta 1Sains, FridayAddition, subtitutionSince /ˈsɪns/, Friday /ˈfɹaɪˌdeɪ/ 2OverloadUnknown wordsOverflowed /ˌoʊvɝˈfɫoʊd/ 3Rajawati,sousReversal, Unknown wordsRawajati, South /ˈsaʊθ/ ClosingLets, English /ˈeŋɡɫɪʃ/unknown word, subtitutionLatest /ˈɫeɪtəst/, English /ˈɪŋɡɫɪʃ/ Table 21 The Identification of the Errors of Student 19Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningEnglish /ˈeŋɡɫɪʃ/Subtitution, English /ˈɪŋɡɫɪʃ/ TitleDozenOmissionDozens /ˈdəzənz/ 1AnnouncedAddition, Announced /əˈnaʊnst/ 2ReportlyOmissionReportedly /ɹiˈpɔɹtədɫi/ 3Rajawati,sousReversal, Unknown wordsRawajati, South /ˈsaʊθ/ ClosingAllsubtitutionAll /ˈɔɫ/ Table 22 The Identification of the Errors of Student 20Paragraph of the TestIdentification of ErrorDescription Error Classification Correction OpeningNews /ˈnjez/SubtitutionNews /ˈnjuz/ TitleAreas /ˈaɹəaz/SubtitutionAreas /ˈɛɹiəz/ 1Announced AdditionAnnounced /əˈnaʊnst/ 2SoutSubtitutionSouth /ˈsaʊθ/ 3Placed /ˈpɫaset/AdditionPlaced /ˈpɫeɪst/ ClosingNe..news /ˈnjuz/repetitionNews /ˈnjuz/ A. SubtitutionThe most subtitution error was made by the student who was initialized “SK” number 6, the student made 37 subtitution errors when read the text.The student did not know how to pronounce a word so made the student pronounce change a letter. Example word ‘’area’’, correct pronunciation in English of the word is ‘’ /ˈɛɹiə/’’ but students kept reading the word with them mother tounge and still like originally them mother tongue is ‘’area’’. Another example word is ‘’news’’, correct pronunciation in English is ‘’ /ˈnjuz/’’ , but the students kept reading with them mother tongue is ‘’news’’.B. AdditionIn this sentence ‘’Dozens of neighborhoods across Jakarta were inundated on Saturday morning following heavy downpour in the upstream area of Bogor in West Java since Friday afternoon’’, the researcher saw the student as ‘’MDR’’ number 14, in the word ‘’upstream’’, the student added ‘’ing’’ and to be ‘’upstreaming’’. And another word ‘’subdistricts’’, the student as ‘’RF’’ number 7, the student added ‘’si” after ‘’sub” and to be ‘’subsidistricts’’.C. OmissionOmission is the third most errors among other types of errors made by students. The word ‘’dozens’’ is a a word that has the most omission errors. The students erased letter ‘’s’’ and just read ‘’dozen’’. And the most omission error was made by student who has initialized ‘’CC’’ number 18, the student made 92 omission errors when read the text. Students not only remove letters in words but students remove words in a sentence. Example is in the first sentence on first paragraph, the students did not read from word ‘’Dozens’’ until ‘’downpour’’. D. RepetitionRepetition error made by students when the students read a word not fluently so that it makes students repeat the pronunciation of the word. The most repetition error was made by the student who was initialized “RF” number 7, the student made 7 repetition errors when read the text. Example word ‘’Katulampa’’, in the first recitation the students faltered so that the student read ‘’Katulu…’’ and next the student made repetition to correct the pronounce and finally the students read ‘’Katulampa’’E. ReversalReversal is reversal of the order in which language units are read. This inversion can be in the form of phoneme, letter or morpheme reversal. Reversal is the least error made by students. Error was made to the word ''Rawajati'', the students read to be ‘’Rajawati’’. F. Unknown WordsUnknown words is results of reading errors that undergo a process of replacing, adding, deleting, repeating or reversing, which results in words not being identified in the target language. Unknown words is the second most errors among other types of errors made by students. The student did not know how to pronounce a word so made the student read with the pronunciation random. Example ‘’inundated’’ , the student has initialized ‘’RA’’ number 16 , the student read to be ‘’intent’’. Another example made by student who has initialized ‘’HW’’ number 4, the student read to be ‘’inaded’’. After determining the error that made by students, the next step was calculating the percentage of all kinds of error to figure out dominant kind of error. Total errors of Subtitution are 400 errors on percentage 37,8%. Total errors of Addition are 62 errors on percentage 5,8%. Total errors of Omission are 210 errors on percentage 19,8%. Total errors of Repetition are 61 errors on percentage 5,7%. Total errors of Reversal are 12 errors on percentage 1,1%. Total errors of Unknown Words are 313 errors on percentage 29,5%. Based on the findings, the students were known that there was some problems in their reading ability. Clark and Clark (1977:271) stated that the causes of error that might cause the students errors which were cognitive and phsycological reason. Based on the interview results, the researcher found those causes of errors influenced the sudents’ ability in reading. Those were classified in the following:A. Cognitive ReasonLack of VocabularyVocabulary is an important skill when reading English in fluently. The students can not reading news item text fluently because some of them feel there are words they rarely hear and some students felt that they could not speak English. The Problems that face with some students were stated in the data or interview, ‘’ Menurut saya karena ada kata-kata yang jarang bahkan tidak pernah didengar’’ and ‘’Karena saya tidak bisa bahasa Inggris’’.Lack of PronunciationFor this case based on experienced by students, one of the problem or causes in their reading error were have poor pronunciation that explained in data interview, ‘’ Menurut saya pengucapan setiap kata dan aksennya’’. The last experiences from respondent related to lack of pronunciation, ‘’Ketika membaca angka, waktu dan kata-kata yang jarang dijumpai’’.B. Phsycological ReasonFeeling NervousThe prevalent problems are faced by students of SMA Swasta Imelda was feeling nervous. This condition like shy uncomfortable as well, or it can be afffected by a person’s emotional state for some reason. The problems related in feeling nervous were stated in data interview, ‘’ Merasa gugup ketika membaca teks berita di kelas’’.Lack of confidenceSome students felt unconfident when they read news item text in class. They are not confident because they are afraid of making mistakes and being noticed by other friends in the class. And the student felt insecure with English skill they have. The problems related in lack of confident were stated in data interview,’’ Merasa tidak percaya diri ketika membaca teks berita di kelas’’.After analyzing the data, it was found that:The occurance of subtitution error was 400, the occurance of addition error was 62, the occurance of omission error was 210, the occurance of repetition error was 61, the occurance of reversal error was 12 and the occurance of unknown words error was 313.The most dominant error made by students in reading news item text was 400 occurences or about 37,8% in subtitution.The Causes of error made by students’ reading news item text is Cognitive reason and Phsycologycal reason. In cognitive reason, most dominant causes of students’ error is lack of pronunciation. And in phsycologycal reason, most dominant causes of students’ error is feeling nervous . CONCLUSIONAfter analyzing the data, some conclusions can be drawn as the following. There were six kinds of errors that the students made namely subtitution, addition, omission, repetition, reversal, and unknown words. Subtitution was the most frequent error made by the XII grade students of SMA Swasta Imelda medan. Total errors of subtitution were on percentage 37,8%. The lowest frequent error was reversal. Total errors of reversal were on percentage 1,1%.Causes of errors in reading news item text encountered by the XII grade students of SMA Swasta Imelda Medan, it was found that there are some reasons or causes of errors in their reading ability, related to cognitive and psychological factors. Among those causes of errors, the major causes encountered by the XII grade students are lack of vocabulary and lack of pronunciation as cognitive reason, feeling nervous and lack of confidence as psychological reason. REFERENCES Abdussamad, Z. 2021. Qualitative Research Methods. Makassar: CV. Syakir Media Press.Ahmad, S. 2019. Error Analysis on Grammar in Writing News Item Text Made by The First Year Students of MA Syekh Subakir Nglegok Blitar. Journal of Development Research, 3 (1), 20-24.Ihdar, C. I. 2021. Improving Reading Aloud Skills Using Picture Story Media in Indonesian Language Subjects for Third Grade Students SDN Kalaserena Kec. Bontonompo Kab. Gowa. Unpublished thesis, Makassar: Faculty of Teacher Training and Education Unversity of Muhammadiyah Makassar.Mia, W. Muhammad, A. H. 2021. Error Analysis on Students’ Translation News Item Text from English to Indonesia. Proceedings of The Tenth International Conference on Languages and Arts (ICLA), 599,128-133.Mutiana, N. Ikeu, K. 2019. The Analysis of Students’ Pronunciation Errors in Reading Aloud. JeTLe, 1(1), 17-20.Montaser, H. A. A. 2020. The Role of Reading Aloud Strategy on EFL Learners in Improving Reading and Pronunciation. Unpublished thesis, Khartoum: Sudan University of Science and Technology College of Graduate Studies.